Spontaneous movement therapy for a young adult with adolescent idiopathic scoliosis: a case report - Zhang, Yi-Heng; Lim, Hyoung-Won (Journal of physical therapy science, 2025)
[Purpose] This case study explored the potential of Spontaneous Movement Therapy (SMT)-an active-modified form of Vojta therapy-in improving spinal alignment parameters in a young adult with a history of Adolescent Idiopathic Scoliosis (AIS). [Participant and Methods] A 21-year-old female with a prior diagnosis of AIS was assessed using full-spine radiographs, which revealed thoracic dextroscoliosis (35.6°) and lumbar levoscoliosis (28.8°). She reported no spinal pain or leg length discrepancy. The patient subsequently underwent an 8-week SMT intervention targeting both coronal and sagittal spinal alignment. [Results] Following the SMT intervention, the thoracic Cobb angle decreased by 4.6° (from 35.6° to 31°), and the angle of trunk rotation (ATR) decreased by 4.0° in the thoracic spine and 3.33° in the lumbar spine. The lumbar Cobb angle remained largely unchanged (28.8° to 29.1°). Although the Cobb angle and ATR were reduced, these changes did not exceed the minimal clinically important difference (MCID). [Conclusion] Although this case report presents promising preliminary observations, the reductions in spinal curvature parameters did not exceed the MCID, suggesting the need for cautious interpretation. Further studies with larger sample sizes and control groups are warranted to validate the clinical effectiveness of SMT in AIS management.